Are project-based organizations willing to learn compliance lessons from sanctioned organizations close to them? The moderating effect of knowledge base compatibility and strength of the event. Issue 6 (August 2021) - Wang, Zhixiu; Yang, Xiaojun; Chan, Albert P.C.; Liu, Junying
Abstract: To crack down on rule violations by organizations, previous studies have mainly advocated improving the deterrent effect of sanctions by increasing punishment and strengthening supervision. However, violations stepping on the 'red line' remain rampant, despite an increasingly serious regulatory environment. In this respect, factors determining an organization's ability to learn from sanctions against others have barely been investigated. To address this issue, this study investigated the deterrent effect of sanctions from the perspective of the social distance between the sanctioned organization and observing organization and explored the moderating effects of knowledge base compatibility, as well as the strength of sanction event. Empirical evidence based on three vignette-based experiments that simulated a multinational project-based organization in the construction industry, a typical industry with serious violations, was sanctioned for failure to comply with host country regulations, showed that the deterrent effect of a sanction event is greater for organizations that are closer to the sanctioned organization than for those that are far from the target. Moreover, when knowledge base compatibility with the sanctioned organization was higher or when the sanction event was more novel, disruptive and critical for observing organizations, the deterrent effect of sanctions was extended and the observing organizations learned more compliance lessons from the sanction. Based on these findings, this study contributes to project governance and provides useful strategies for regulators and policymakers to control violations by expanding the deterrent effect of sanctions.